Analysis of factors influencing stunting prevention among indigenous Papuan pregnant women in Jayapura City - Yulia Nuradha Kartosiana Wasaraka; Iin Ariyani; Soalihin Soalihin; Danang Riyanto; Neng Ratih Widiyastuti; Nurul Fauziah Handayani (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Indigenous Papuan communities maintain strong cultural traditions, which deeply influence daily life including practices around pregnancy and childbirth. These traditions are one factor being examined in relation to the high rate of stunting in Papua Province, which exceeds the national average. Previous research shows that low education, limited access to health, economics and culture influence the behavior of pregnant women. Objective: This study analyzes the factors related to stunting prevention among Indigenous Papuan pregnant women in Jayapura City. Methods: This research method used a quantitative analysis with a cross-sectional approach. The sampling technique used was non-probability sampling with a snowball method, totaling 50 pregnant women from OAP who live in the community in the Jayapura City area, Papua. Data collection used a questionnaire instrument. Bivariate analysis used chi-square. Results: The results indicate that cultural values (0.017) and family support (0.000) show a statistically significant association with stunting prevention practices. However, access to and utilization of formal health services did not demonstrate a significant association (0.638). Conclusion: This finding suggests that current health services may not be optimally aligned or effectively delivered to support stunting prevention within this community. Moving forward, a more integrative approach is needed. Engaging community and religious leaders will be essential to bridging cultural understandings with public health goals, thereby enabling healthcare systems to contribute more effectively to reducing stunting among Indigenous Papuans.